2003
DOI: 10.1126/science.1083413
|View full text |Cite
|
Sign up to set email alerts
|

Transcription Start Regions in the Human Genome Are Favored Targets for MLV Integration

Abstract: Factors contributing to retroviral integration have been intractable because past studies have not precisely located genomic sites of proviruses in sufficient numbers for significant analysis. In this study, 903 murine leukemia virus (MLV) and 379 human immunodeficiency virus-1 (HIV-1) integrations in the human genome were mapped. The data showed that MLV preferred integration near the start of transcriptional units (either upstream or downstream) whereas HIV-1 preferred integration anywhere in the transcripti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

96
1,120
7
13

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,216 publications
(1,236 citation statements)
references
References 17 publications
96
1,120
7
13
Order By: Relevance
“…In contrast to the genomic integration profile of retroviral systems and other transposon systems ( piggyBac and Tol2 ), which show integration preferences for actively transcribed genes,51, 52, 53 SB -based integration is random 37, 54. Compared to computationally generated control datasets, SB100X -mediated genomic integration of the PEDF gene delivered by the pFAR4 vector into primary human RPE cells showed a close-to-random profile.…”
Section: Discussionmentioning
confidence: 83%
“…In contrast to the genomic integration profile of retroviral systems and other transposon systems ( piggyBac and Tol2 ), which show integration preferences for actively transcribed genes,51, 52, 53 SB -based integration is random 37, 54. Compared to computationally generated control datasets, SB100X -mediated genomic integration of the PEDF gene delivered by the pFAR4 vector into primary human RPE cells showed a close-to-random profile.…”
Section: Discussionmentioning
confidence: 83%
“…In a large series of HPV-associated tumors, viral integration sites were found preferentially distributed in transcribed cellular sequences (Klimov et al, 2002;Wentzensen et al, 2002;Ziegert et al, 2003). Extensive analyses of retrovirus integration sites have shown that active genes (Schroder et al, 2002) or transcription start regions (Wu et al, 2003) are preferential integration targets. Fragile sites have also been reported to facilitate HPV DNA integration (Thorland et al, 2003), but other factors may influence the nature of the genetic rearrangements that implicate insertion of foreign DNA and illegitimate recombination.…”
Section: Discussionmentioning
confidence: 99%
“…The numerous proteins that have been suspected to influence integration can be grouped into three main categories: those that (i) interact with IN directly; (ii) bind to the viral DNA to influence the process; or (iii) participate in the final gap repair step. Of equivalent interest is deciphering the roles cellular proteins are likely to play in genome-wide patterns of retroviral integration [34][35][36][37][38][39][40][41][42][43][44][45][46]. Experimental capabilities in this area changed with the availability of the human genome sequence, commensurately advancing bioinformatics, and more recently, a second wave of high-throughput sequencing methodologies [47,48]).…”
Section: Host Cell Factors and Integrationmentioning
confidence: 99%
“…Broadly sketched, lentiviruses favor integrating in active transcription units without favoring the promoter regions in particular [34,35,38,39,43,45,46], MLV favors the promoter regions of genes (transcription start sites and CpG islands) [35,38], and ALV appears, in general, to show less specificity for transcription units [36,37,42]. MMTV shows none at all and is so far the most random integrator [57].…”
Section: Host Cell Factors and Integrationmentioning
confidence: 99%